Mechanical considerations of the continuum for rigid bodies and fluid-structure interactions - SEKHAR, CHINTA; BASHA, SK HUSSIAN (The journal of contemporary issues in business and government, 2019)
Continuum mechanical issues for both deformable and rigid solids, as well as fluids, are discussed in this study. All systems are approximated using the same finite element method. Particularly, we provide a standard displacement-based formulation for the deformable solids and use this framework to describe the transformation of the solid into a rigid body in the limit of infinite stiffness. Last but not least, we show how to immerse a discretized solid into a fluid for fluid-structure interaction issues.